GROWTH RESPONSE, NUTRIENT DIGESTIBILITY AND COST ANALYSIS OF WEST AFRICAN DWARF BUCKS FED DIETS CONTAINING GRADED LEVELS OF COWPEA (Vigna unguiculata) HUSK WITH GMELINA (Gmelina arborea) LEAVES AS BASAL DIET - Oloche, Juliana; Dido, P. L.; Ayoade, J. A. (FUDMA JOURNAL OF SCIENCES, 2021)
A total of twenty (20) growing WAD bucks of about 7 - 9 months and having average weight of 9.64 kg were used in an 84 day trial to investigate the performance response of West African Dwarf (WAD) goats fed diets containing cowpea husk (CPH). Cowpea husk used for the study was collected from Nasarawa Eggon Local Government Area of Nasarawa State. Four experimental diets were formulated to replace maize offal with cowpea husk and designated A (0%), B (25%), C (50%), and D (75%) and used to feed the bucks. Results showed that none of the performance parameters showed treatment effect (P>0.05). The mean daily weight gain was 56.55 g/day, 52.75 g/day, 42.81 g/day and 50.49 g/day for diets A, B, C and D respectively. The mean daily feed intake ranged between 458.40 g/day -503.00 g/day, with treatments D and B having the highest and lowest numerical values, respectively. The apparent nutrient digestibility coefficient of dry matter (DM), crude fibre (CF), ash, nitrogen free extract (NFE) showed significant differences (P<0.05) among the treatments and some crude fibre fractions like neutral detergent fibre (NDF) and acid detergent lignin (ADL) were significantly different (P<0.05) among the treatments means. The concentrate feed cost/kg diet was between ₦63.85-₦73.74. The cost/kg weight gain was best for treatment B (₦617.05). The production efficiency was less than one for all the treatments. Cowpea (vigna unguiculata) husk can be used in the diets of West African dwarf goats without adverse effect on the performance indices and profitability.